The birth of viromics: an interview with Forest Rohwer. (October 2018) - Greenway, Alice; Rohwer, Forest
The editor of Future Microbiology, Alice Greenway, speaks to Forest Rohwer from San Diego State University (CA, USA) following his talk entitled 'Counting all the world's phage' at ASM Microbe 7–11 June 2018.